Investigation of covers and chemical treatment for the suppression of cyanobacteria in water treatment systems. (19th October 2020) - Box, Justin; Otto, John; Kent, William; Higgins, Brendan T.
Abstract: Algal growth in water treatment plants can lead to the introduction of toxin and odour compounds from cyanobacteria and causes filter fouling. Here, we investigate the use of woven polypropylene covers and a proprietary copper sulfate formulation (EarthTec) to prevent algal growth within mesocosms designed to simulate settling basins. Chlorophyll a, soluble nutrients, weather patterns and cyanobacterial gene abundance were measured. The covers suppressed algal and cyanobacterial growth in mesocosms, likely due to a combination of light blockage and prevention of insects from entering the mesocosms. In contrast, mesocosms amended with EarthTec exhibited little difference from the control mesocosms in terms of algal growth. qPCR analysis revealed that only a small fraction of cyanobacteria in the system contained genes necessary for the production of the microcystin toxin. Despite differences between mesocosms and full‐scale settling basins, the data here suggest that woven covers can suppress algal growth while minimising evaporative water losses.